Plant Breeding in the Omics Era - Ortiz Ríos, Rodomiro (Springer International Publishing : Imprint: Springer, 2015)
This book provides analysis of plant breeding and its role for producing high-yielding cultivars that increase farming profitability and sustainability. This work analyzes the past and present of plant breeding, while providing research that investigates the future of crop improvement. Plant breeding today, as it was before, depends on crop biodiversity and its sustainable use, which can be further facilitated by advances in omics and bioinformatics. It starts with assessing plant genetic resources (wild species, landraces, obsolete cultivars, genetic stocks) variation aiming to enhance the cultigen pool. Research on genetics-aided by current omic tools- should lead to designing a knowledge-based plant breeding, which could bring further genetic gains in the breeding pools. Plant breeding, however, will increasingly require pursuing a holistic interdisciplinary approach based on integrated system-oriented thinking.